2012
DOI: 10.1063/1.3701719
|View full text |Cite
|
Sign up to set email alerts
|

Stark shifts and exciton dissociation in CdSe nanoparticle grafted conjugated polymer

Abstract: Exciton dissociation and charge trapping at poly(3-hexylthiophene)/phenyl-C61-butyric acid methyl ester bulk heterojunction interfaces: Photo-induced threshold voltage shifts in organic field-effect transistors and solar cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Generally, the intensity of absorption increases with increasing pH and a rise in intensity suggests an enhancement in the AgNPs formation with time. [ 12 ] At pH 12, higher intensity was observed and the maximum absorption was 404 nm after 2 and 4 h of reaction time. Therefore, the obtained results confirm that basic pH is more suitable for the synthesis of QE‐AgNPs.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the intensity of absorption increases with increasing pH and a rise in intensity suggests an enhancement in the AgNPs formation with time. [ 12 ] At pH 12, higher intensity was observed and the maximum absorption was 404 nm after 2 and 4 h of reaction time. Therefore, the obtained results confirm that basic pH is more suitable for the synthesis of QE‐AgNPs.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of nanoparticles is increasing exponentially because of its wide range of applications in the field of optoelectronics, biosensors, bio-nanotechnology, biomedicine etc. (Bharali, Sahoo, Mozumdar, & Maitra, 2003;Mehata, Majumder, Mallik, & Ohta, 2010;Mehata, 2012Mehata, , 2015Ratnesh & Mehata, 2015;Saxena, Mozumdar, & Johri, 2006;Subbiah, Veerapandian, & Yun, 2010). Various physical and chemical methods have been formulated for the synthesis of nanopartilces of desired shape and size.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the study of CdS nanocrystallites prepared by using different capping ligands opened new avenues to control the size and structure of CdS nanoparticles, which further produces a significant modification in spectroscopic properties. Furthermore, application of an external electric field plays a decisive role in understanding electronic structure and excited-state dynamics of the small size such as nanometer size materials Q-dots as well as large molecules such as polymers and protein 5 7 13 14 15 16 17 18 19 20 21 .…”
mentioning
confidence: 99%
“…The application of an external field to the optical transitions provides important information about the charge-transfer reaction and molecular motion 13 14 15 . This also provides information about the reliability and stability of organic light emitting diode (OLEDs) 20 21 or polymer light emitting diode (PLED) 16 17 , and more efficiently accelerated and decelerated electron transfer processes in molecular systems 14 . It has been observed that the PL of CdS and cadmium telluride (CdTe) nonoparticles is quenched by the application of external electric field, indicating that applied electric field influence the excited-state dynamics of nanomaterials 5 7 18 .…”
mentioning
confidence: 99%